Syphilis incidence among men who have sex with men in China: results from a meta-analysis. (February 2017) - Chen, Guohong; Cao, Ya; Yao, Yuan; Li, Ming; Tang, Weiming; Li, Jianjun; Babu, Giridhara R; Jia, Yue; Huan, Xiping; Xu, Genxing; Yang, Haitao; Fu, Gengfeng; et al.
The recent upsurge of syphilis infections among men who have sex with men (MSM) is one of the major challenges facing China. However, the overall burden is still not clear. This study aims to summarize the incidence of syphilis among MSM in China by using meta-analysis. We comprehensively searched PubMed-MEDLINE, China National Knowledge Infrastructure and Chinese Wanfang databases. Articles published between December 2009 and March 2015 that met the inclusion criteria were considerably involved in this meta-analysis. Two reviewers performed a quality assessment of the studies and extracted data for estimating the overall syphilis incidence. STATA 12.0 was used to summarize the overall incidence of syphilis. In all, 14 studies from 13 papers were included in this study. Follow-up duration of these studies ranged from six to 36 months, while drop-out rates ranged from 11.9% to 83.6%. The individual incidence rates of the included studies varied from 3.1/100 person-years (95% CI, 0.8–5.3/100 person-years) to 38.5/100 person-years (95% CI, 28.9–48.1/100 person-years), with a pooled incidence of 9.6/100 person-years (95% CI, 7.0–12.2/100 person-years). The subgroup meta-analysis revealed that incidence estimates were 38.5/100 person-years (95% CI, 28.9–48.1/100 person-years), 12.1/100 person-years (95% CI, 7.0–17.2/100 person-years), 11.2/100 person-years (95% CI, 0.7–23.1/100 person-years), 8.9/100 person-years (95% CI, 6.5–11.2/100 person-years), 5.7/100 person-years (95% CI, 3.4–8.0/100 person-years) and 3.1/100 person-years (95% CI, 0.8–5.3/100 person-years) in Northeast, North, Southwest, East, South and Northwest China, respectively. Syphilis incidence among Chinese MSM is high, and this may increase the spread of other sexually transmitted infections, including human immunodeficiency virus. It is essential to integrate syphilis control programs with HIV control programs. This can be achieved by establishing public health response systems to monitor and control the epidemic of syphilis and HIV together in China.